Feasibility Study of Using Energy Extracted from The Process of Electrochemically Consumed of Al 2024 for Powering Daily Used Electric Car - Marda, Yanuar Mohamad; Riastuti, Rini; Ibrahim, Muhammad Hamka (UI Scholars Hub, 2024)
Usage of green energy for transportation has become important due to the contribution of transportation activity to climate change. Electrochemical energy has been used as a source of green energy. The objective of this work is to evaluate sufficiency of energy provided by electrochemically consumed Al 2024 for supplying energy to daily used PHEV electric car. Study of previous articles, observation of typical amount of energy required, electrochemical galvanic cell experiments, and simple calculations have been conducted to determine produced energy feasibility. Electrical energy produced by consuming 340 gr of Al 2024 in galvanic cells has the total lifetime of 10.8 hours and the mileage covered on the electric vehicle mode is 234.9 km. It can be used to cover most of the energy needed for a daily combination of sub-urban and urban city car.